Village Land Administration as an Effort to Prevent Agrarian Disputes/Conflicts - Sri Wahyu Handayani; Supriyanto Supriyanto; Manunggal Kusuma Wardaya; Wismaningsih Wismaningsih; Weda Kupita (Universitas Muhammadiyah Purwokerto, 2023)
This study criticizes village land administration policies that have not been orderly and firm. This resulted in the emergence of agrarian disputes/conflicts. The village land administration policy has not regulated sanctions if the regulation is not implemented. This normative research is complemented by empirical research using the interview method with village officials and Focus Group Discussion in Jompo Kulon Village, Sokaraja District. Based on the identification of research results with empirical methods in Jompo Kulon Village, it was found that several causes of problems that arise, including the limitations of Human Resources who master technology and do not understand the bookkeeping of land administration, land administration which is still manual, only refers to the Letter C Book so there is a chance for errors. in recording and lack of public awareness to register their land. Based on the results of the Focus Group Discussion, this study offers a solution for the standardization of village land administration records which are carried out digitally to minimize data changes and the existence of rewards and punishments for those who do not standardize the village administration records and encourage village community awareness to register their land through the Land Registration Program. Complete Systematic.Keywords: village land administration; agrarian; dispute; conflict